The relationship between cognitive flexibility and the syntactic level in children with language delay between (4 and 6) years: a field study at Constantine - Boukhdenna, Mounir; Ghesmi, Amel (Journal of Human Sciences, 2022)
This study targets the relationship between cognitive flexibility and morphosyntax in children with language delay between 4 and 6 years, the sample was composed of 24 children in Constantine, the study was based on control tools, and tools to measure the variables, we followed the descriptive analytical approach, the results showed that there was no correlation between cognitive flexibility and understanding 1, but 'there was between cognitive flexibility and repetition of utterance with a Degree 0.05 and the production of utterance with 0.01, we concluded that there is a partial correlation between cognitive flexibility and morphosyntax, which leads us to rethink the evaluation method. Instead of going directly to language, we can work on other functions such as cognitive flexibility to assess and develop them because of their correlation with language.